Case Report: Ovarian endometrioid tumor occurring in a patient with early-stage, low-risk endometrial carcinoma successfully treated by fertility-sparing management - Tian, Shuxu; Song, Huangbei; Wang, Fang; Hao, Juan; Liu, Xuan; Geng, Chenchen (Frontiers in Oncology, 2025)
RationaleEndometrial carcinoma (EC) increasingly affects younger women, prompting interest in fertility-sparing treatments. Although hormonal therapy is a feasible option for carefully selected patients, there remains a substantial risk of recurrence or associated ovarian malignancy.Case presentationA 35-year-old premenopausal woman reported abnormal uterine bleeding characterized by increased menstrual flow over approximately one year.Diagnosis and interventionShe was diagnosed with stage IA, grade 1 EC managed initially with high-dose oral megestrol acetate followed by a levonorgestrel-releasing intrauterine system due to intolerance. Serial endometrial biopsies demonstrated histologic remission, after which the patient elected definitive surgery with hysterectomy and bilateral salpingectomy while preserving the ovaries. Uterine pathology confirmed absence of residual carcinoma.Follow-up and outcomesDuring follow-up, a right adnexal cystic-solid mass was detected and categorized as Ovarian-Adnexal Reporting and Data System (O-RADS) ultrasound category 4, with MRI features raising suspicion. Comprehensive surgical staging confirmed a unilateral low-grade ovarian endometrioid carcinoma with squamous differentiation; staging and peritoneal cytology were negative. The patient recovered uneventfully and remains under surveillance without adjuvant therapy.LessonsThis case highlights the rare occurrence of metachronous ovarian endometrioid carcinoma after successful fertility-sparing and hysterectomy, underscores the importance of shared decision-making regarding ovarian preservation, and supports risk-adapted surveillance strategies in this population.